Field of bones - Jance, Judith A. (New York : William Morrow, an imprint of HarperCollins Publishers, 2019)
Sheriff Joanna Brady's best intentions to stay on maternity leave take a hit when a serial homicide case rocks Cochise County, dragging her into a far-reaching investigation to bring down a relentless killer in this chilling tale of suspense.
Includes recipe and A Look Back by J.A. Jance
Keywords: Brady, Joanna -- (Fictitious character) -- Fiction; Sheriffs -- Arizona -- Fiction; Detective and mystery fiction